2015
DOI: 10.1016/j.cegh.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the magnitude, distribution and determinants of catastrophic health expenditure in urban Lucknow, North India

Abstract: Available online xxxKeywords: Catastrophic health expenditure Determinants Out of pocket payment Hospitalization India a b s t r a c t Introduction: To assess the magnitude, distribution, and determinants of catastrophic health expenditures (CHE) of households in urban Lucknow, North India.Methods: A cohort of 400 households was selected by 2-step cluster sampling and baseline demographic survey was done followed by two six-monthly health surveys. CHE was defined as health expenditures !10% of household's capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…A total of 25 studies investigated the relationship between family size and incurring CHE ( 15 , 16 , 18 22 , 24 28 , 31 – 43 ). Five studies found that the relationship is not significant ( 16 , 19 , 36 , 38 , 41 ), ten studies found that a large family size is a risk factor ( 18 , 20 , 22 , 24 , 26 , 31 , 32 , 34 , 35 , 40 ) and ten found that a small family size is associated with a higher risk ( 15 , 21 , 25 , 27 , 28 , 33 , 37 , 39 , 42 , 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 25 studies investigated the relationship between family size and incurring CHE ( 15 , 16 , 18 22 , 24 28 , 31 – 43 ). Five studies found that the relationship is not significant ( 16 , 19 , 36 , 38 , 41 ), ten studies found that a large family size is a risk factor ( 18 , 20 , 22 , 24 , 26 , 31 , 32 , 34 , 35 , 40 ) and ten found that a small family size is associated with a higher risk ( 15 , 21 , 25 , 27 , 28 , 33 , 37 , 39 , 42 , 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…Targeted protection interventions are highly expected (Pal ; Misra et al . ). Even if universal coverage is a promising development, the specific disease programme should continue to be subsidised.…”
Section: Discussionmentioning
confidence: 97%
“…; Misra et al . ), and indirect and coping costs (Laokri et al ., ) must be addressed. Further analysis of the long‐term consequences of potentially irreversible coping strategies is needed to comprehensively apprehend illness poverty gap.…”
Section: Discussionmentioning
confidence: 99%
“…The low level of public spending and high cost-sharing, result in very high rates of catastrophic expenditures for the Indian people. 39 , 46 50 …”
Section: Resultsmentioning
confidence: 99%